Clonidine Premedication Reduces Maternal Requirement for Intravenous Morphine After Cesarean Delivery Without Affecting Newborn's Outcome. Issue 5 (1st September 2001) - Yanagidate, Fumi; Hamaya, Yoshihiro; Dohi, Shuji
Abstract : Background and Objectives: The α2 -agonist clonidine has several benefits for patients undergoing surgery. During and after elective cesarean delivery (C-section), we assessed the condition of parturient and neonate when one half of the parturients were pretreated with oral clonidine. Methods: Forty-six consenting parturients were studied in a randomized, double-blinded manner. Preanesthetic medication was atropine and famotidine with or without clonidine 4 μ g/kg. After baseline measurements in parturients and fetuses, combined spinal and epidural anesthesia was established (1.6 mL of 0.5% tetracaine diluted with 10% dextrose in water). C-section was performed while breathing oxygen spontaneously (3 L/min) through a facemask. After delivery, neonates were assessed at 1 and 5 minutes, and the condition of mother and neonate was observed for 48 hours. Results: Parturients receiving clonidine showed no hemodynamic instability during and after C-section, and while their visual analog scale (VAS) scores, verbal descriptive scale (VDS) scores, and sedation scores did not differ from those without clonidine, they needed significantly less patient-controlled analgesia (PCA) morphine for postoperative pain for the first 2 days ( P < .01). Fetal heart rate, umbilical artery and vein pH and gas tensions, and the Apgar-scores of the newborns showed no intergroup differences. No neonatal depression or bradycardia was observed for 48 hours after delivery. Conclusion: The present results indicate that oral clonidine reduces the PCA morphine requirement after C-section without compromising the condition of the fetus or newborn. Further study including larger number of patients would be needed before we conclude that oral clonidine for parturients is safe for their newborns.